Karakterisasi Plasma Nutfah Kacang Tanah (Arachis hypogaea L.) Lokal Asal Bangka Berdasarkan Karakter Morfologi: Karakterisasi Plasma Nutfah Kacang Tanah (Arachis hypogaea L.) Lokal Asal Bangka Berdasarkan Karakter Morfologi - Riwan Kusmiadi; Gigih Ibnu Prayoga; Fitra Apendi; Alfiansyah Alfiansyah (Universitas Bangka Belitung, 2018)
Groundnut production can be improved through the use of superior seeds derived from landrace germplasm. The aim of this research was to study the morphological characteristics of Bangka landrace groundnut and the relationship between landrace. This research was conducted in Experimental and Research Garden, Bangka Belitung University from March to August 2017. This research used RBD with 9 landrace accessions and 1 national variety as treatment. The 9 landraces are accession Bedeng Akeh, Lubuk kelik, Matras, Sungailiat, Arung Dalam, Belimbing, Jongkong, Air Ketimbai 1, and Air Ketimbai 2. National variety is Kancil variety. The analysis of genetic relationship was done by the UPGMA method. The result of morphological characterization shows many similarities in the character such as growth habit, number of branches, stem color, leaf color, standard petal color, pod beak, and seed color. The differences are leaflet shape, pod constriction, pod reticulation, and primary seed color. The result of relationship analysis based on morphological characterization showed 4 groups on 87% similarities. The first group consists of the accession of Belimbing, Jongkong, Air Ketimbai 2, Sungailiat, and Kancil varieties. The second group is accession Matras, Lubuk Kelik, and Bedeng Akeh. The third group is Air Ketimbai 1 and the fourth group is Arung Dalam accession.